A Comprehensive Analysis of Renewable Energy Based on Integrating Economic Cybernetics and the Autoregressive Distributed Lag Model—The Case of Romania - Androniceanu, Armenia; Georgescu, Irina; Nica, Ionuț; Chiriță, Nora (Energies (Basel), 2023)
Renewable energy represents a crucial resource in the efforts to combat climate change and reduce dependence on fossil fuels. In the past few decades, Romania has lessened its environmental footprint and played an important role in actions against climate change. In this research, the energy sector in Romania is analyzed from a holistic perspective as a complex adaptive system by using econometric tools. The purpose of the research is to analyze the Romanian energy sector as a cybernetic system and to study the long-run and the short-run causal impact of greenhouse gas emissions (GHG) and renewable energy (RE) on real GDP per capita. The causality among GHG, foreign direct investment (FDI), RE, and real GDP is checked by means of the autoregressive distributed lag model (ARDL). The time series are extracted from Eurostat and OECD databases and cover the period 2000-2021. The results reveal that (i) the variables are cointegrated according to the ARDL bounds test; (ii) in the long run, GHG negatively impacts GDP, RE positively impacts GDP; (iii) in the short run, GHG and RE positively impact GDP; (iv) the speed of adjustment is around 32%. The study holds significance both for scholars and the policy makers from the governmental environment agencies that should decide how to effectively reduce GHG emissions, promote renewable energy adoption, and design policies to facilitate the transition to a low-carbon economy.